Jurnal Kata: the fall of emily grierson: a jungian analysis of a rose for emily - Chenghsun hsu, Ya huei wang (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
this paper discusses the tragic life of faulkners emily grierson, a life dominated by patriachy and traditional southern social values